Morphological Characters, Dry Matter Production, and Nutritional Quality of Cowpea (Vigna unguiculata L.) as Influenced by Genotype and Environment - Alemayehu Abebe Lemore; Mulisa Faji Dida; Kedija Ahmed Seid (Advances in Agriculture)
Cowpea is an important grain legume crop used as feed for livestock, and its dry beans provide protein. Consequently, the objective of this study was to evaluate selected cowpea genotypes for herbage dry matter yield and nutritional quality in two agro-ecologies of the Benishangul-Gumuz region. The study was conducted at Kamashi and Assosa forages research stations of Assosa Agricultural Research Center, and the sites were purposively selected to represent lowland and midland agro-ecologies, respectively. Four cowpeas’ accessions (V. Unguiculata ILRI-11114, ILRI-12688, ILRI-12713, and ILRI-9333) and one check (Melka (ILRI-9334) as a check) were evaluated in a randomized complete block design with three replications. Herbage dry matter yield, plant height at forage harvesting, and days to maturity were significantly affected by location (L). Longer plant heights, shorter days to maturity, and higher dry matter yield (P<0.001) were recorded at Kamashi than at Assosa. Herbage dry matter yield was significantly P<0.05 affected by year (Y), Y∗L (Y and L interaction), G∗L∗Y (genotype (G), L and Y interaction), and G∗L. Hebage dry matter yield was similar between years at Assosa, whereas at Kamashi significantly (P<0.001) different and more yields were obtained in 2015. The genotypes did not differ in nutritional quality parameters such as ash, acid detergent fibre, crude protein, and organic matter digestibility (P>0.05). However, neutral detergent fibre and acid detergent fibre were significantly (P<0.05) influenced by genotype. Thus, from the present study, it can be recommended that cowpea genotypes ILRI-12688 are suitable for Assosa and ILRI-11114 to Kamashi areas in terms of biomass production.